The Role of High-Density Lipoprotein in COVID-19 - Wang, Guyi; Deng, Jiayi; Li, Jinxiu; Wu, Chenfang; Dong, Haiyun; Wu, Shangjie; Zhong, Yanjun (Frontiers in Pharmacology, 2021)
The current Coronavirus disease 2019 (COVID-19) pandemic has become a global challenge. Managing a large number of acutely ill patients in a short time, whilst reducing the fatality rate and dealing with complications, brings unique difficulties. The most striking pathophysiological features of patients with severe COVID-19 are dysregulated immune responses and abnormal coagulation function, which can result in multiple-organ failure and death. Normally metabolized high-density lipoprotein (HDL) performs several functions, including reverse cholesterol transport, direct binding to lipopolysaccharide (LPS) to neutralize LPS activity, regulation of inflammatory response, anti-thrombotic effects, antioxidant, and anti-apoptotic properties. Clinical data shows that significantly decreased HDL levels in patients with COVID-19 are correlated with both disease severity and mortality. However, the role of HDL in COVID-19 and its specific mechanism remain unclear. In this analysis, we review current evidence mainly in the following areas: firstly, the pathophysiological characteristics of COVID-19, secondly, the pleiotropic properties of HDL, thirdly, the changes and clinical significance of HDL in COVID-19, and fourthly, the prospect of HDL-targeting therapy in COVID-19 to clarify the role of HDL in the pathogenesis of COVID-19 and discuss the potential of HDL therapy in COVID-19.